Anti-Corrosion and Mechanical Performance of Graphene Oxide and Reduced Graphene Oxide Multi-Layer Coatings Applied to Nickel-Titanium Via Dip-Coating - Pablo Forlam Ribeiro Batista; Hana Hitomi Koga; Victor Cardoso Campideli; Dalila Chaves Sicupira; Leandro de Arruda Santos (Materials Research)
This study investigated the mechanical and anti-corrosive properties of two graphene derivatives multi-layer coatings applied to a superelastic NiTi alloy. Several aspects of the coating process and electrochemical characterization remain unclear, including the impact of a multilayer during dip-coating on the final morphology and corrosion resistance of the system. Additionally, the relationship between long-term immersion tests, mechanical cycling and the anti-corrosion performance of these coatings requires further investigation. The coatings were formulated with GO and rGO dispersed in SEBS to be deposited as flexible nanometer films on NiTi wires using the dip-coating technique. The coating characterization was conducted through scanning electron microscopy, atomic force microscopy, X-ray diffraction and energy dispersive scattering. The mechanical performance under superelastic loading-unloading cycles was evaluated using uniaxial tensile tests. Potentiodynamic polarization and electrochemical impedance spectroscopy analyses were employed to assess corrosion. The potentiodynamic polarization results demonstrated an enhancement in corrosion resistance for the coated samples, particularly in specimens coated with rGO. Additionally, electrochemical impedance spectroscopy analysis revealed superior performance of the coating containing GO after 21 days of immersion in a simulated body fluid. These findings represent an advancement in the investigation of the NiTi surface modification by graphene derivatives.